2013
DOI: 10.3163/1536-5050.101.4.013
|View full text |Cite
|
Sign up to set email alerts
|

Development of the research lifecycle model for library services

Abstract: Input from researchers was the most effective tool for developing the model. A flexible research lifecycle model can be developed to match the needs of different service groups and the skills of different librarians.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 14 publications
(13 reference statements)
1
27
0
1
Order By: Relevance
“…Boote and Beile (2005) have made a valuable contribution in this arena with their analysis of what constitutes "good research. " There has been a focus in recent years on how to refine academic services required to support the research lifecycle (Todd, 2012;Vaughan et al, 2013;Deng & Dotson, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Boote and Beile (2005) have made a valuable contribution in this arena with their analysis of what constitutes "good research. " There has been a focus in recent years on how to refine academic services required to support the research lifecycle (Todd, 2012;Vaughan et al, 2013;Deng & Dotson, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Vaughan et al (2013) used the research life-cycle model to analyze services at a large university in the U.S., and Ina Fourie and Suzanne Bakker (2012) reported on a service model for a manageable research cycle which was pioneered at the Central Cancer Library of the Netherlands Cancer Institute. Moving on to research that has been conducted in Chinese libraries , Pang Bei (2012) found that the librarian's role has already been transformed to the extent that it is much more integral to the work of the researchers, and required to provide support at each stage of research cycles.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This model takes into account the different disciplines of the researchers and provides active, positive in-depth, personalized and convenient services for the researchers. In areas with a longer established tradition of the subject service or "liaison" model, research university libraries offer intensive research support services not only as an important part of library services but also as a strategic development plan for the whole library (Cornell University Library, 2011), and researchers have investigated the utility of these services through a research life-cycle model (Vaughan et al, 2013). But this type of investigation has not been carried out before in China.…”
Section: Introductionmentioning
confidence: 99%
“…Libraries are accordingly moving into areas such as funding opportunities and grant writing, ethics review, data curation and repository management, poster design and conference hosting (physical and virtual), journal and monograph publishing, bibliometric evaluation and impact assessment (Adema & Schmidt, 2010;Carroll, 2011a;Crow et al, 2012;Delserone, Kelly, & Kempf, 2010;Drummond & Wartho, 2009;Furlough, 2010;Healy, 2010;Herther, 2009;Lyon, 2012;McBain, Culshaw, & Walkley Hall, 2013;Vaughan et al, 2013), alongside their established roles in collection stewardship, resource procurement and information literacy. The development of support for the management of research data in line with national policy is a particular concern (Carlson & Kneale, 2011;Gold, 2007;Lynch, 2008;Lyon, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…There is a perceived requirement for libraries to develop more specialized interventions to provide point-of-need research support and advice around the whole knowledge creation cycle: from ideas generation and project conception, through data acquisition, manipulation and interpretation, to the deposit of results, publication of findings, and assessment of impact (Larsen & Riis, 2012;MacColl & Jubb, 2011;Vaughan et al, 2013). Libraries are accordingly moving into areas such as funding opportunities and grant writing, ethics review, data curation and repository management, poster design and conference hosting (physical and virtual), journal and monograph publishing, bibliometric evaluation and impact assessment (Adema & Schmidt, 2010;Carroll, 2011a;Crow et al, 2012;Delserone, Kelly, & Kempf, 2010;Drummond & Wartho, 2009;Furlough, 2010;Healy, 2010;Herther, 2009;Lyon, 2012;McBain, Culshaw, & Walkley Hall, 2013;Vaughan et al, 2013), alongside their established roles in collection stewardship, resource procurement and information literacy.…”
Section: Introductionmentioning
confidence: 99%